The Importance of Being First: Exploring Priority and Diversity Effects in a Grassland Field Experiment - Weidlich, Emanuela W. A.; von Gillhaussen, Philipp; Delory, Benjamin M.; Blossfeld, Stephan; Poorter, Hendrik; Temperton, Vicky M. (Frontiers in Plant Science, 2017)
Diversity of species and order of arrival can have strong effects on ecosystem functioning and community composition, but these two have rarely being explicitly combined in experimental setups. We measured the effects of both species diversity and order of arrival on ecosystem function and community composition in a grassland field experiment, thus combining biodiversity and assembly approaches. We studied the effect of order of arrival of three plant functional groups (PFGs: grasses, legumes and non-leguminous forbs) and of sowing low and high diversity seed mixtures (9 or 21 species) on species composition and aboveground biomass. The experiment was set up in two different soil types. Differences in PFG order of arrival affected the biomass, the number of species and community composition. As expected, we found higher aboveground biomass when sowing legumes before the other PFGs, but this effect was not continuous over time. We did not find a positive effect of sown diversity on aboveground biomass (even if it influenced species richness as expected). No interactions were found between the two studied factors. We found that sowing legumes first may be a good method for increasing productivity whilst maintaining diversity of central European grasslands, although the potential for long-lasting effects needs further study. In addition, the mechanisms behind the non-continuous priority effects we found need to be further researched, taking weather and plant-soil feedbacks into account.